PEMBUATAN HAND SANITIZER BERBASIS BAHAN ALAM DI DESA TATAH LAYAP, KALIMANTAN SELATAN ERA PANDEMI COVID-19 - Dwi Rizki Febrianti; Rakhmadhan Niah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
During the pandemic the need for hand sanitizer became the basic needs of the world community. Maintaining hygiene and health protocols are top priorities to avoid exposure to covid-19. The training on making Natural Hand Sanitizer in Tatah Layap Village, Banjar Regency is expected to increase community creativity to support the economy and community protection materials during the Covid-19 pandemic. The main materials made in this training are from natural materials that are around the village environment, Betel and Lemongrass. Through this training, people have more knowledge about business opportunities that can be created through creativity and skills so that the hand sanitizer they make can have value. The training is carried out through several stages, namely by providing materials and knowledge, in the implementation of the training, participants will be guided. Then the results can be utilized by the community for daily life and become a superior product.